MEMAHAMI ISU-ISI AKTUAL DALAM STUDI ISLAM ABORSI, HAM, GENDER, DAN DEMOKRASI - Anita Anita; Nia Sukmawati, Syafatin (ADISAM PUBLISHER, 2026)
Developments in the world of Islamic thought, recorded in history, show that Islam has provided a unique style according to the conditions of its time. Whether it is in the form of a kind of vision, method, and frame of mind that differs from one thought to another. Modernization has given birth to various forms of change, both structural and cultural. From the information above, there are several things that underlie the issues in Islamic studies. So this will be discussed in a paper entitled